Green synthesis of silver nanoparticles using aqueous extract of Stachys lavandulifolia flower, and their cytotoxicity, antioxidant, antibacterial and cutaneous wound‐healing properties. (1st July 2019) - Zangeneh, Mohammad Mahdi; Joshani, Zeinab; Zangeneh, Akram; Miri, Elnaz
Abstract : In a biological process where the herbal tea ( Stachys lavandulifolia ) aqueous extract was applied as a capping and reducing agent, nanoparticles (NPs) of silver (Ag) were synthesized. These AgNPs were characterized using Fourier transform‐infrared spectroscopy, field emission‐scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, transmission electron microscopy and ultraviolet–visible spectroscopy. The synthesized AgNPs had great cell viability dose‐dependently [investigating the effect of the plant on human umbilical vein endothelial cell line] and indicated this method was non‐toxic. In this study, the 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) free radical scavenging test was carried out to examine antioxidant properties, which revealed similar antioxidant properties for AgNPs and butylated hydroxytoluene. Agar diffusion tests were applied to determine the antibacterial characteristics. The macro‐broth tube test was run to determine minimum inhibitory concentration. All data of antibacterial and cutaneous wound‐healing examinations were analyzed by SPSS 21 software (Duncan post hoc test). AgNPs showed higher antibacterial property than all standard antibiotics ( p ≤ 0.01). Also, AgNPs prevented the growth of all bacteria at 2–8 mg/ml concentrations and destroyed them at 2–16 mg/ml concentrations ( p ≤ 0.01). For the in vivo experiment, after creating the cutaneous wound, the rats were randomly divided into six groups: untreated control; treatment with Eucerin basal ointment; treatment with 3% tetracycline ointment; treatment with 0.2% AgNO3 ointment; treatment with 0.2% S. lavandulifolia ointment; and treatment with 0.2% AgNPs ointment. These groups were treated for 10 days. For histopathological and biochemical analysis of the healing trend, a 3 × 3‐cm section was prepared from all dermal thicknesses at day 10. Use of AgNPs ointment in the treatment groups substantially reduced ( p ≤ 0.01) the wound area, total cells, neutrophil, macrophage and lymphocyte, and remarkably raised ( p ≤ 0.01) the wound contracture, hydroxyl proline, hexosamine, hexuronic acid, fibrocyte and fibrocytes/fibroblast rate compared with other groups. Seemingly, AgNPs can be used as a medical supplement owing to their non‐cytotoxic, antioxidant, antibacterial and cutaneous wound‐healing properties. Abstract : Green synthesis of silver nanoparticles by Stachys lavandulifolia.